Prognostic impact of HNF4α expression in interstitial lung disease. Issue 1 (13th October 2021) - Sawazumi, Tomoe; Baba, Tomohisa; Iwasawa, Tae; Arai, Hiromasa; Matsumura, Mai; Takemura, Tamiko; Sugiyama, Misaki; Sekiya, Motoki; Saigusa, Yusuke; Ogura, Takashi; Inayama, Yoshiaki; Ohashi, Kenichi; et al.
Abstract: Pneumocyte injury is a crucial factor influencing the severity of interstitial lung disease (ILD). In this study, we investigated the potential of hepatocyte nuclear factor α (HNF4α) as an immunohistochemical marker to detect pneumocyte injury and as a prognostic marker. Surgical lung biopsy specimens were collected from 309 patients with different types of ILDs (61 idiopathic pulmonary fibrosis (IPF), 173 non‐IPF, and 75 unclassifiable ILD). HNF4α expression were examined and the frequency of positive cells (per mm 2 ) was calculated. HNF4α was strongly expressed in regenerating pneumocytes present on fibroblastic foci, Masson bodies/organizing alveoli. In the non‐IPF and unclassifiable ILD groups, cases with high frequency expression showed significantly poorer outcome. Particularly, in the unclassifiable ILD group, the prognostic impact was more significant (death due to ILD, log‐rank test, p  < 0.0001), with a 10‐year survival rate (hazard ratio 11.1, Wald test, p  = 0.0003), as compared to the non‐IPF group (log‐rank test, p = 0.0269; hazard ratio 2.7, Wald test, p = 0.0334) . Multivariable analysis focusing on the unclassifiable ILD group confirmed that the frequent HNF4α expression was an independent prognostic factor (hazard ratio 28.6; Wald test, p  = 0.0033). Thus, HNF4α can be utilized as an immunohistochemical marker for pneumocyte injury and have prognostic impact particularly in unclassifiable ILD.